2016
DOI: 10.1017/s1360674316000113
|View full text |Cite|
|
Sign up to set email alerts
|

Analyzing lexical emergence in Modern American English online

Abstract: This article introduces a quantitative method for identifying newly emerging word forms in large time-stamped corpora of natural language and then describes an analysis of lexical emergence in American social media using this method, based on a multi-billionword corpus of Tweets collected between October 2013 and November 2014. In total 29 emerging word forms, which represent various semantic classes, grammatical parts-ofspeech and word formation processes, were identified through this analysis. These 29 forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 38 publications
2
84
0
4
Order By: Relevance
“…Specifically, we identified potential emerging word forms in the corpus following the procedure described in Grieve et al (2017). First, we extracted the word forms that occurred at least 500 times in the complete corpus, which amounted to 97,246 distinct types.…”
Section: Finding Emerging Wordsmentioning
confidence: 99%
“…Specifically, we identified potential emerging word forms in the corpus following the procedure described in Grieve et al (2017). First, we extracted the word forms that occurred at least 500 times in the complete corpus, which amounted to 97,246 distinct types.…”
Section: Finding Emerging Wordsmentioning
confidence: 99%
“…Lexical change online Language changes constantly, and one of the most notable forms of change is the adoption of new words (Metcalf, 2004), sometimes referred to as lexical entrenchment (Chesley and Baayen, 2010). New nonstandard words may arise through the mutation of existing forms by processes such as truncation (e.g, favorite to fave; Grieve et al, 2016) and blending (e.g., web+log to weblog to blog; Cook and Stevenson, 2010). The fast pace and interconnected nature of online communication is particularly conducive to innovation, and social media provides a "birds-eye view" on the process of change (Danescu-Niculescu-Mizil et al, 2013;Kershaw et al, 2016;Tsur and Rappoport, 2015).…”
Section: Related Workmentioning
confidence: 99%
“…In our previous research on lexical innovation, we identified 54 emerging words in a 9 billion word corpus of geocoded American Twitter collected between October 2013 and November 2014 (Grieve et al 2017. These 54 emerging words, which are listed in Table 1, grew steadily in popularity on Twitter in 2014 and represent a wide range of different parts-of-speech, semantic domains, and word formation processes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, based on an analysis of a 9-billion-word corpus of American Twitter, we identified 54 newly emerging words, which were very uncommon at the end of 2013 but whose usage increased substantially over the course of 2014 (Grieve et al 2017;Grieve et al 2018). By extracting a relatively large sample of emerging words, we have been able to make general claims about the form, function, and origin of new word formations in Modern American English.…”
Section: Introductionmentioning
confidence: 99%